Level of Complexity in Utilizing SOLO Taxonomy Among Grade Six Pupils At Callejon Elementary School - DUMARAOS, JUN (International Journal of Arts, Sciences and Education, 2022)
Abstract The main objective of this study was to find out the level of complexity in utilizing SOLO Taxonomy in Science among Grade VI pupils of Callejon Elementary School. The study used the descriptive method employing the purposive sampling among 36 Grade VI pupils of Callejon Elementary School. The main instrument used was the validated Teacher-made test questions focusing on Science VI Quarter 1 competency “Describing techniques in separating mixtures”. The relevant data were treated statistically using weighted mean score and Likert Scale for data interpretation. The result showed that the use of SOLO taxonomy as an assessment tool can provide the teachers significant information about how well the pupils understand a topic thus allowing him to provide appropriate remedial instructions or intervention program.